Market Structure Analysis in Local Stimulants Marketing Among Women in Osun State, Nigeria - Akerele, Ezekiel Olaoluwa; Akanni, K.A.; Oyebanjo, O.; Agbaje, E.M. (Acta Universitatis Danubius. Œconomica, 2023)
This study investigated the structure and marketing efficiency of local stimulants in selected Local Government Area of Osun State, Nigeria. A total of two hundred and forty (240) respondents was sampled. Structured questionnaires was used in obtaining data from the respondents. Specifically, the study described the socio-economic characteristics of the respondents, examined the market structure for local stimulants, the marketing margin, marketing efficiency, examined the degree of market concentration for the marketers of the local stimulants and described the constraints encountered in the marketing of local stimulants in the study area. Results from the study revealed that majority (75.8%) of the respondents had at most primary school education earning at least N53,321 per month. The market structure of local stimulants in the study revealed that kolanut was the most traded with a typical kola nut marketer selling about 3.88591 tonnes (i.e 388,591kg) per month. Analysis of the marketing margin of the local stimulants revealed that typical retailers earned N323.50, N274.40, N162.50, N285.65 and N33.26 per Kilogram for bitter kola, kolanut, ginger, alligator pepper and pepper respectively. The marketing efficiencies is between 2.48 and 4.62 across markets for all the stimulants. An evaluation of market concentration revealed that pepper stimulant have the highest market concentration of 2,083 while bitter kola had the least market concentration of 871 across the LGAs. High transportation (51.5%) and middlemen rip-offs (42.6%) constituted the most common challenges confronting the respondents while low demand (3.3%) was the least challenge or constraint faced by local stimulant marketers. Therefore, in order to ensure a better marketing efficiency for the local stimulants in the study area, farmers should seek help from cooperative societies, borrowing through soft loans from commercial banks or government parastatals and ministries such as ministry of commerce trade, and industries to source more funds.